2005
DOI: 10.1007/s00125-005-1935-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro neogenesis of human islets reflects the plasticity of differentiated human pancreatic cells

Abstract: Aims/hypothesis: The neogenesis of islets from cultured human adult pancreatic tissue has been reported. The islet progenitors have been thought to be ductal cells. Since previous experiments have been 'contaminated' by a number of pre-existing islet cells, we examined their involvement in islet cell neogenesis. Methods: Fresh human pancreatic cells with different purities of islet cells were grown in monolayer culture and labelled with bromodeoxyuridine. Transitional cells were analysed by double immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 32 publications
(53 reference statements)
0
57
0
Order By: Relevance
“…Thus, the expansion of cells derived from the islet-depleted exocrine fraction, which is usually discarded following isolation, has been shown to give rise to a near homogeneous population of CK19-positive epithelial cells, with minimal fibroblast contamination during the initial phase of culture [21,25]. Although it is not possible to completely eliminate endocrine components from the initial plated material, previous studies have shown that such culture conditions are not conducive either to the adherence or prolonged survival of native islet cells [25] and that any endocrine cells that do exist become de-differentiated within 3-4 days of monolayer culture [24,29]. In our study we found that over 90% of the cells derived from the outgrowth cultures were positive for CK19 at the time of the initiation of the islet-DEC co-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expansion of cells derived from the islet-depleted exocrine fraction, which is usually discarded following isolation, has been shown to give rise to a near homogeneous population of CK19-positive epithelial cells, with minimal fibroblast contamination during the initial phase of culture [21,25]. Although it is not possible to completely eliminate endocrine components from the initial plated material, previous studies have shown that such culture conditions are not conducive either to the adherence or prolonged survival of native islet cells [25] and that any endocrine cells that do exist become de-differentiated within 3-4 days of monolayer culture [24,29]. In our study we found that over 90% of the cells derived from the outgrowth cultures were positive for CK19 at the time of the initiation of the islet-DEC co-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used magnetic cell sorting to obtain non-endocrine CK19-enriched cell populations by eliminating NCAM-positive cells [10]. However, the use of CA19-9 microbeads allows much more efficient purification of ductal cells, as described previously [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Human islets Islets were isolated as described earlier [10]. Informed consent was obtained from tissue donors and institutional Ethics Committees in Uppsala and Helsinki approved all procedures.…”
Section: Methodsmentioning
confidence: 99%
“…However, in that study, transdifferentiated acinar cells or dedifferentiated ␤-cells could have developed an epithelial (CK19 ϩ ) phenotype during shipment from isolation centers or during the 4-day culture in G418, used to eliminate mesenchymal cells. Gao et al (28) suggested that the insulin ϩ cells may have been derived from the residual ␤-cells in their preparations, since depletion of neural cell adhesion molecule (NCAM) ϩ cells, which were presumed to be only islet cells, resulted in few insulin ϩ cells. However, while NCAM is expressed selectively in rodent islets, we found that in human pancreas, NCAM was also expressed at both the mRNA and protein level in the duct epithelium (S.B.-W., C. Nienaber, unpublished data).…”
Section: Discussionmentioning
confidence: 99%